(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
The exchange rate and controlling its fluctuations is a critical issue for most countries, especially developing ones. Fluctuations in the Iraqi currency exchange rate against foreign currencies, particularly the US dollar, have preoccupied the thinking and policies of successive governments. Due to the rentier nature of the Iraqi economy, the supply of foreign currency differs from the demand for it. This is in addition to other issues that emerged after the political change in 2003. These issues ranged from the printing of national currency abroad, the lack of control over all border crossings, and the inability to directly deposit all oil revenues into national accounts. This was compounded by negative transactions resulting from the mechanism for selling foreign currency through the Central Bank of Iraq’s window and the adoption of unsound financing methods, which affected exchange rates. The figure is a prominent factor in the sharp fluctuations. The researchers used simple regression to measure the impact of total sales through the currency selling window on the nominal and parallel exchange rates using the statistical program AMOS VS.23. The research yielded a set of findings, the most important of which is that Iraq’s reliance on the foreign exchange window as a primary source of financing foreign trade. The lack of transparency and adequate oversight has led to increased demand for the dollar and increased volatility in the parallel exchange rate, negatively impacting the stability of the Iraqi economy. Consequently, the research produced a number of recommendations, most notably the need to shift from reliance on the foreign exchange window to more transparent and efficient methods of financing foreign trade, such as letters of credit. This should also include strengthening oversight of foreign currency flows and linking all commercial and financial outlets under a unified management system under the supervision of the Central Bank and the Ministry of Finance